Theoretical Foundations of Digital Content Integrity Expertise - Bobok I.I.; Kobozieva A.A. (Problems of the Regional Energetics)
In the context of the rapid development of information technologies, their implementation in the process of functioning of critical infrastructure, in particular energy, of any state is extreme-ly relevant. At the same time, the continuity and quality of functioning of any automated system in the digital space critically depends on ensuring the integrity of the information used. The ef-fectiveness of digital content integrity expertise methods is determined by their theoretical foun-dations. Existing theoretical approaches do not allow obtaining a final solution to this problem. The aim of this work is to develop a general approach to the analysis of the state of information systems, based on the theory of matrices, for its use in the examination of the integrity of digital content. The objective was achieved by investigating the perturbation properties of singular val-ues and singular vectors of the image (or video frame) matrix as a result of perturbation for orig-inal and non-original contents. The most important results of the work are: substantiation for non-original content of the destruction of the monotony of the trend of the function of depend-ence of the disturbance of the singular number on its number, which takes place for original content; substantiation of the fundamental possibility of estimating the magnitude of the perturb-ing effect. The significance of the obtained results lies in their subsequent use for the develop-ment of universal methods for examining the integrity of digital images, video, in particular ste-ganoanalytical methods, which make it possible not only to identify the fact of integrity viola-tion, but also to assess the magnitude of the perturbing effect, which is extremely important in steganoanalysis, where this value characterizes the throughput of a hidden communication channel.